The Role of Online Reviews as a Mediator in The Decision to Purchase Fashion Products at Shopee: Systematic literature review (SLR) - Utami, Rizki Amalia; Soetjipto, Budi Eko; Wardana, Ludi Wishnu (Economics and Business Journal (ECBIS), 2025)
The development of digital technology has transformed consumer consumption patterns, particularly in the fashion industry, which is increasingly dominated by e-commerce platforms. Shopee, as one of the largest marketplaces in Southeast Asia, has become a primary choice for consumers when shopping for fashion products. One factor influencing consumer purchasing decisions is the availability of online reviews on the platform. This study aims to analyze the role of online reviews as a mediating variable in fashion product purchasing decisions on Shopee. Online reviews serve as a source of information that helps consumers evaluate product quality, seller reputation, and the level of satisfaction of previous users. The research method used was a quantitative approach, distributing questionnaires to Shopee consumers who had previously purchased fashion products. The collected data was then analyzed using a path analysis model to examine the direct and indirect relationships between factors influencing purchasing decisions. The results show that online reviews play a significant role as a mediator in the decision-making process. Consumers tend to trust other users' real-life experiences more than solely the seller's product description. Positive reviews increase consumer interest and confidence in a product, while negative reviews can delay or even cancel a purchase decision. These findings confirm that the presence of online reviews is not only a supporting factor but also serves as a bridge, mediating the relationship between consumer perceptions of a product and the final purchase decision. The implication of this research is that sellers on Shopee need to pay attention to product and service quality to generate positive reviews, thereby increasing purchase conversion rates.